Chrysopidae family and flower strips as habitat management practices for the control of cabbage insect pests - Alcala Herrera, Rafael; Cotes, Belen; Porcel Vilchez, Mario (Department of Environmental Protection, Estación Experimental del Zaidín - EEZ, 2024)
Flowering plant species within a cultivated field are increasingly implemented as an eco-scheme to re-establish functional agrobiodiversity providing shelter, overwintering sites, and alternative prey and food resources to natural enemies (predators and parasitoids). We evaluated the effect of sown flower strips designed to attract and support natural enemies of Brassica oleracea pests, with a special emphasis on green lacewings (Chyrsopidae). Brassica plant blocks with adjacent flower strips were compared with control plant blocks. Flower strips were comprised by six plant species (Borago officinalis L., Coriandrum sativum L., Fagopyrum esculentum Moench, Foeniculum vulgare Mill., Helianthus annuus L. and Phacelia tanacetifolia Benth.) which provides floral resources with demonstrated positive effects on survival, reproduction, development and recruitment of lacewings. The abundance of the five pest species considered in this study (Mamestra brassicae, Plutella xylostella, Pieris brassicae, P. rapae and Brevicoryne brassicae) was significantly higher in control blocks (9.32 ± 3.11) than in blocks next to the flower strips (4.06 ± 0.89). In the flower strips, parasitoid and predator abundances increased significantly with increasing blooming rates of the selected flowering species. Chrysoperla carnea (Stephens, 1836) sensu Henry and Chrysoperla lucasina (Lacroix, 1912) represented 90.8% of the total green lacewing adults collected from flower strips. In laboratory and field conditions, green lacewings clearly preferred pollen from P. tanacetifolia and C. sativum, being the consumption of pollen grains significantly higher for females compared to male specimens. In conclusion, flower strips may have a positive effect on biological pest control in brassica crops. Indeed, the use of flower strips may be an alternative to pesticide applications, creating a more favourable environment for locally occurring natural enemies that have the potential to control key brassica pests. P. tanacetifolia is pointed out as a particularly suitable plant to increase the presence of C. carnea in agricultural fields. Enhancing natural enemy biodiversity by using flower resources, as observed for green lacewings, can increase the resilience of natural pest control and provide additional ecosystem services such as pollination. As a general recommendation, we encourage researchers, farmers and practitioners to include the establishment of flower strips in their integrated pest management programs as a promising tool to protect functional biodiversity for biocontrol.